PV system way of the future - Gomes, Isaías (2021)
This chapter is a synthesis about the solar resource aiding in the way of a sustainable future uphold by photovoltaic conversion of solar energy into electric energy. A view is presented about: irradiance and irradiation on the earth; current and emerging technology of photovoltaic systems; hot-spot effect due to shading on photovoltaic systems; job creation potential; electronic power inverter; and issues concerning the integration of photovoltaic systems into the electric grid.